Liquidity and Company Size Impact on Capital Structure with Profitability Mediation - Yusuf, Muhammad; Dyarini, Dyarini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study examines and analyzes the effect of liquidity and firm size on capital structure, with profitability as a mediating variable in mining companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023. Capital structure is crucial in balancing debt and equity to support company operations and investments. According to the Pecking Order Theory, firms with high liquidity tend to rely on internal financing, whereas the Trade-Off Theory suggests that larger firms find it easier to access external funding at lower costs. This study analyzes seven causal relationships among liquidity, firm size, profitability, and capital structure. The research employs a quantitative approach using panel data regression analysis and the Fixed Effect Model (FEM). The sample was selected through purposive sampling, consisting of 10 mining companies that met specific criteria. Data processing is conducted using EViews version 12. The independent variables in this study are liquidity and firm size, while capital structure serves as the dependent variable, with profitability acting as a mediating variable. The results indicate that liquidity negatively affects both profitability and capital structure, whereas firm size positively influences profitability and capital structure. Profitability negatively impacts capital structure and mediates the relationship between liquidity and capital structure. However, profitability does not significantly mediate the relationship between firm size and capital structure. These findings have implications for companies in optimizing their capital structure management and for investors in assessing corporate financing policies for investment decisions.